Dehydrogenation kinetics, reversibility, and reaction mechanisms of reversible hydrogen storage material based on nanoconfined MgH2−NaAlH4. (December 2015) - Plerdsranoy, Praphatsorn; Meethom, Sukanya; Utke, Rapee
Abstract: Studies of dehydrogenation kinetics, reversibility, and reaction mechanisms during de/rehydrogenation of nanoconfined MgH2 −NaAlH4 into carbon aerogel scaffold (CAS) for reversible hydrogen storage material are for the first time proposed. Two different MgH2 :NaAlH4 molar ratios (1:1 and 2:1) of hydride composite are melt infiltrated into CAS under 1:1 (CAS:hydride composite) weight ratio. Successful nanoconfinement is confirmed by N2 adsorption−desorption. Multiple-step dehydrogenation of milled samples is reduced to two-step reaction due to nanoconfinement. Peak temperatures corresponding to main dehydrogenation of nanoconfined samples significantly reduce as compared with those of milled samples, i.e., ∆ T =up to 50 and 34 °C for nanoconfined sample with 1:1 and 2:1 (MgH2 :NaAlH4 ) molar ratios, respectively. Hydrogen content released (the 1 st cycle) and reproduced (the 2 nd, 3 rd, and 4 th cycles) of nanoconfined samples enhance up to 80% and 68% with respect to theoretical hydrogen storage capacity, respectively, while those of milled samples are 71% and 38%, respectively. Remarkable hydrogen content reproduced after nanoconfinement is due to the fact that metallic Al obtained after dehydrogenation ( T =300 °C under vacuum) of nanoconfined samples prefer to react with MgH2 and produces Al12 Mg17, favorable for reversibility of MgH2 −NaAlH4 system, whereas that of milled samples stays in the form of unreacted Al under the same temperature and pressure condition. Highlights: First time report on nanoconfined MgH2 −NaAlH4 . Effects of MgH2 :NaAlH4 molar ratio on nanoconfinement and hydrogen sorption. Reduction of dehydrogenation temperature (Δ T up to 50 °C) after nanoconfinement. 80% and 68% released and reproduced from nanoconfined samples after 4 cycles.